2020
DOI: 10.1007/s00109-020-01878-y
|View full text |Cite
|
Sign up to set email alerts
|

ASK1 inhibition: a therapeutic strategy with multi-system benefits

Abstract: p38 mitogen-activated protein kinases (P38α and β) and c-Jun N-terminal kinases (JNK1, 2, and 3) are key mediators of the cellular stress response. However, prolonged P38 and JNK signalling is associated with damaging inflammatory responses, reactive oxygen species-induced cell death, and fibrosis in multiple tissues, such as the kidney, liver, central nervous system, and cardiopulmonary systems. These responses are associated with many human diseases, including arthritis, dementia, and multiple organ dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
79
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 118 publications
(205 reference statements)
1
79
0
Order By: Relevance
“…65 It should also be highlighted that there were no significant adverse events seen in the treatment group and the number of participants that had an improved WHO functional class was notably higher in the treatment groups (14-19%) when compared to the placebo group (3%). 65 Conclusion ASK1-dependent stress-signalling pathways are known to be critical in the remodelling processes observed in PAH. Here, the selective ASK1 inhibitor (GS-444217) reduced lung vascular remodelling and subsequently RVSP in a SuHx model of PH.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…65 It should also be highlighted that there were no significant adverse events seen in the treatment group and the number of participants that had an improved WHO functional class was notably higher in the treatment groups (14-19%) when compared to the placebo group (3%). 65 Conclusion ASK1-dependent stress-signalling pathways are known to be critical in the remodelling processes observed in PAH. Here, the selective ASK1 inhibitor (GS-444217) reduced lung vascular remodelling and subsequently RVSP in a SuHx model of PH.…”
Section: Discussionmentioning
confidence: 90%
“…65 It should also be highlighted that there were no significant adverse events seen in the treatment group and the number of participants that had an improved WHO functional class was notably higher in the treatment groups (14–19%) when compared to the placebo group (3%). 65…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This study provides new insights into the links between PM2.5 and OA. ASK1 activation is a critical mediator of cell death and inflammation (Ogier, Nayagam, & Lockhart, 2020). ASK1 activation is triggered by various forms of cellular stress such as the influx of calcium ions, Fas ligand expression, tumor necrosis factorrelated apoptosis, and oxidative stress, which activate the MAPK pathway (Ogier et al, 2020;Tesch, Ma, & Nikolic-Paterson, 2016).…”
mentioning
confidence: 99%
“…Thus, other therapeutic strategies are needed to reduce the renal injury via the JNK/c-Jun pathway. On this point, apoptosis signal-regulating kinase 1 (ASK1), the member of the mitogen-activated protein kinase kinase kinase (MAPKKK) family, is another candidate to regulate the JNK/c-Jun pathway [44]. Accumulating evidence revealed that ASK1 activation accelerates renal injury through the activation of p38 and JNK cascades in rodent models of kidney injury, including ischemia/reperfusion-induced AKI, unilateral ureteric obstruction, and diabetic nephropathy [45][46][47], and that treatment with GS-444217, an inhibitor of ASK1, limited the loss of podocytes most likely through the anti-apoptosis pathway in a diabetic kidney disease mouse model, indicating ASK1 as an important target for podocyte injury [48].…”
Section: Discussionmentioning
confidence: 99%